Minerva in Colours: First Results on a Polychrome Roman Sculpture from Carnuntum (Pannonia) - Gabrielle Kremer; Robert Linke; Georg Plattner; Eduard Pollhammer; Marina Brzakovic; Robert Krickl; Nirvana Silnovic; Václav Pitthard (Heritage, 2023)
This paper presents the first results of a current interdisciplinary research project on the polychromy of Roman provincial stone artefacts in selected areas of the Danubian provinces (PolychroMon). The statuary group of Minerva and the Genius immunium from Carnuntum (Archaeological Museum Carnuntinum inv. CAR-S-48) is dated to the second half of the second century AD and still retains traces of the original polychromy. The aim was to focus on non-invasive techniques and to employ micro-invasive methods for necessary cross-checking and gaining information otherwise not accessible. The investigation revealed that paint was applied on a layer of white lime wash. Additionally, the object shows several traces of Egyptian blue, which was mainly detected in Minerva’s and the Genius’ clothes. Other pigments whose traces were found on the sculpture include green earth, yellow and red ochre, as well as red lead and carbon black. Microscopic analysis confirms the presence of modern-age compounds as well (barium sulphate and zinc oxide) used for modern retouches. Gas chromatography–mass spectrometry revealed the use of egg as the major proteinaceous binding medium in the red lead polychromy.